HUBUNGAN PENGETAHUAN PENATALAKSANAAN FARMAKOLOGI DENGAN NILAI TEKANAN DARAH PADA PENDERITA HIPERTENSI - Veroneka Yosefpa Windahandayani; Wira Marlinta Ningsi; Yohana Hesti Mordo Ningrum (JURNAL RISET RUMPUN ILMU KESEHATAN, 2022)
Hypertension is a cardiovascular disease with a systolic blood pressure value of 140 mmHg and a diastolic blood pressure value of 90 mmHg. The prevalence of hypertension globally according to WHO is 22% of the total world population. Hypertension cases if not handled properly can cause death, so it is important for hypertensive patients to have good knowledge about hypertension management, especially pharmacological management. The method in this research is descriptive correlation, using a cross sectional approach. The number of respondents in the study were 45 respondents, the sampling technique used purposive sampling. The research data were analyzed using SPSS with the Kendall's-tau correlation test, the results obtained p-value 0.236 > 0.05, meaning that there was no relationship between knowledge of pharmacological management and blood pressure values in patients with hypertension. The implication of this study is that it is hoped that people with hypertension will not only have knowledge, but also have good behavior in taking drugs, and following a low-salt diet.